State Capitalism or Popular Convergences - Latorre, Sara (2009)
This article analyses the interactions between the current government and the anti-mining movement between 2006 and 2009. The main hypothesis of the article holds that the neodevelopmentalist model adopted by the government has given way to new forms of social conflict. On the one hand, the nature of this social conflict is marked by the overwhelming popularity of the government. On the other hand however, the anti-mining movement has been weakened by problems related to its organization, leadership and strategies, which have, in turn, prevented its consolidation.